Amphibian assemblages and diversity patterns in two forest ecosystems of South‐Eastern Nigeria. (13th August 2020) - Rahman, Md Mizanur; Nneji, Lotanna M.; Adeniyi, Adeola C.; Chen, Jinmin; Eniang, Edem A.; Oladipo, Segun O.; Olatunde, Omotoso; Onadeko, Abiodun B.; Kilunda, Felista Kasyoka; Ayoola, Adeola O; Adedeji, Babatunde E.; Nneji, Ifeanyi C.; et al.
Abstract: Despite recent anthropogenic interference, south‐eastern (SE) Nigeria historically hosts a myriad of pristine forest habitats that could sustain diverse amphibian assemblages. Currently, land conversion of primary forests through human activities has led to modified habitats, such as agricultural fields and secondary forest. This calls for biodiversity documentation and initiation of conservation plans. However, the dearth of herpetological studies has limited knowledge of the amphibian species richness and distribution patterns in some forest ecosystems of SE Nigeria. Thus, we surveyed two less‐explored intact forests in SE Nigeria—Afi Forest Reserve (AFR) and Ikpan forest ecosystem (IFE)—to document the patterns of amphibian diversity and distribution. Specimens were searched for opportunistically using visual and acoustic survey methods. Literature searches were conducted to document additional species that were not encountered. Using the observational records and arrays of diversity indices, the patterns of species richness and abundance across habitat types were evaluated. The result of our study revealed the presence of 30 and 31 amphibian species from AFR and IFE, respectively. Our field collections included two unidentified species ( Sclerophrys sp. and Hyperolius sp.) from AFR and one ( Phrynobatrachus sp.) from IFE. Analyses revealed high species diversity and richness in forest and swamps compared with the agricultural field and savannah. Given the increased human activities and the antecedent threats to forest ecosystems of SE Nigeria, we offer recommendations for the initiation of conservation plans for these two surveyed localities. Résumé: Malgré de récentes interférences anthropiques, le sud‐est (SE) du Nigéria héberge historiquement une myriade d'habitats forestiers vierges qui pourraient entretenir diverses populations d'amphibiens. Actuellement, la conversion des terres des forêts primaires par les activités humaines a eu pour résultat des habitats modifiés, tels que les champs agricoles, la forêt secondaire, etc. Cela nécessite une documentation sur la biodiversité et le lancement de plans de conservation. Cependant, le manque d'études herpétologiques a limité la connaissance de la richesse des espèces d'amphibiens et des modèles de distribution dans certains écosystèmes forestiers du sud‐est du Nigéria. Nous avons donc étudié deux forêts intactes moins explorées dans le sud‐est du Nigéria ‐ la réserve forestière d'Afi (AFR) et l'écosystème forestier d'Ikpan (IFE) – afin de documenter les modèles de diversité et de répartition des amphibiens. Les spécimens ont été recherchés de manière opportuniste à l'aide de méthodes d'étude visuelles et acoustiques. Des recherches documentaires ont été menées pour documenter d'autres espèces qui n'ont pas été rencontrées. Les modèles de richesse et d'abondance des espèces dans tous les types d'habitats ont été évalués à l'aide d'enregistrements d'observation et de tableaux d'indices de diversité. Le résultat de notre étude a révélé respectivement la présence de 30 et 31 espèces d'amphibiens de l'AFR et de l'IFE. Nos échantillonnages effectués sur le terrain comprenaient deux espèces non identifiées ( Sclerophrys sp . et Hyperolius sp. ) de l'AFR et une ( Phrynobatrachus sp. ) de l'IFE. Les analyses ont révélé une grande diversité et richesse des espèces dans les forêts et les marécages par rapport au champ agricole et à la savane. Compte tenu de l'augmentation des activités humaines et des menaces antérieures pesant sur les écosystèmes forestiers du sud‐est du Nigeria, nous proposons des recommandations pour le lancement de plans de conservation pour ces deux localités étudiées.